PEMBELAJARAN PRAKARYA DALAM MEMBUAT KERAJINAN BAHAN LUNAK DI KELAS VIII 1 SMP NEGERI 5 PADANG PANJANG - Seli Julita Sari; Asmidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the learning process and artistic outcomes from working with soft materials (clay) in the handicrafts lessons for Class VIII 1 at SMP Negeri 5 Padang Panjang under the Merdeka Curriculum. This study employs a qualitative method, whereby the researcher conducted fieldwork by collecting data through observation, interviews, literature review, and documentation. This handicrafts lesson was conducted over 8 sessions. Each session consisted of several stages: (1) Preparation, namely the preparation of the lesson plan and materials; (2) Introduction, namely taking attendance and saying a prayer; (3) Main activity, namely a lecture, question and answer session, and group practice making wall decorations from clay; (4) Conclusion, namely evaluation and setting homework. The research results show that students were able to produce six wall decoration pieces with diverse themes, such as floral landscapes and the underwater world. It is hoped that this research will provide theoretical and practical contributions to craft teachers.